What made people (more) positive toward the COVID-19 vaccine? Exploring positive and negative deviance perspectives - Mitchell A. M. Matthijssen; Mariëlle Cloin; Florian van Leeuwen; Ien van de Goor; Peter Achterberg (BMC Public Health)
Abstract Background Despite the associations of certain beliefs and worldviews (e.g., religiosity and belief in conspiracy theories) with non-vaccination behavior, some individuals who hold these views still choose vaccination, and vice versa. This study aims to explore why individuals choose to be vaccinated against COVID-19, despite holding opposing beliefs and worldviews, or refrain from doing so, when their beliefs align with vaccination. By examining both positive and negative deviant behavior, we seek to identify strategies and barriers for public health officials to develop interventions to improve vaccination uptake. Methods We conducted semi-structured online interviews with 21 Dutch adults aged 28–75 years (13 positive deviants and 8 negative deviants) between January and July 2022. Interviewees were recruited on the basis of their response patterns in a survey that was part of a larger project on understanding vaccine hesitancy in the Netherlands. The interviews focused on how they formed their intention toward the COVID-19 vaccine and what could change it in the future. The data were analyzed via semi-inductive coding with Atlas.ti.23. Results Positive deviants got vaccinated because they perceived COVID-19 as a threat, wanted to protect (vulnerable) others, or wanted to regain their freedom. Negative deviants did not get vaccinated because they did not perceive the vaccine as appropriate, the disease not as a threat, for religious reasons, or did not trust the authorities. The most important barriers and strategies that were identified that could improve vaccination uptake were unrelated to underlying beliefs and worldviews but related to characteristics of the vaccine such as effectiveness and (potential) side-effects. Conclusion This study demonstrates the applicability of traditional health psychology models, such as the health belief model, in explaining deviant vaccination behavior. Additionally, leveraging prosocial motivations and imposing restrictions on non-vaccinated individuals have been effective strategies for promoting vaccination uptake, albeit restricted to pandemic contexts. As some individuals will remain resistant to vaccination efforts, tailored interventions for vaccine-hesitant individuals may yield greater success rather than attempting to persuade strict opponents of vaccination.